HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN KUALITAS TIDUR PADA MAHASISWA SEMESTER 3 PRODI ILMU KESEHATAN MASYARAKAT - Jilly Angle Priskila Rengkuan; Nancy Sylvia Bawiling; Maxi Moleong (Yayasan Syalom Cipta Sumikolah, 2024)
Social media is software that allows individuals and communities to gather, share, communicate, and sometimes collaborate and play with each other. social media often becomes a platform where students face social pressure, competition or high expectations. This can increase levels of anxiety and stress, dependence on social media can lead to behavior that disrupts sleep and can affect sleep quality. This research aims to determine the relationship use of social media and sleep quality among SME students at Manado State University in 2024. This study used a non-experimental quantitative design with a cross sectional approach with a population of 154 people where a sample of 60 students was taken using random techniques sampling. The research results found that the use of social media in the active category was (81.7%) and the quality of sleep in the poor category was (73.3%). The chi square test results statistically found a value of p = 0.001, (p = <0.05). This means that there is a relationship between the use of social media and the quality of sleep among IKM students at Manado State University. It is hoped that the campus can provide continuous information on the negative effects of using social media over a long period of time